2022
DOI: 10.1002/cyto.a.24667
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 27‐color panel for the detection of measurable residual disease in patients diagnosed with acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) measurable residual disease (MRD) evaluated by multiparametric flow cytometry (MFC) is a surrogate for progression‐free and overall survival in clinical trials and patient management. Due to the limited number of detection channels available in conventional flow cytometers, panels used for assessing AML MRD are typically split into multiple tubes. This cripples the simultaneous and correlated assessment of all myeloblast measurements. In response, we prototyped a single‐tube 27‐col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The feasibility of using high‐parameter panels in clinical practice raises concerns regarding the acquisition of spectral references and the quality control and stability of antibody cocktails. Recent evidence suggests potential cocktail instability within a short period of only 24 h after preparation [33]. Therefore, it is essential to establish the quality of the antibody cocktail for clinical use, whether conventional or spectral flow cytometry is used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of using high‐parameter panels in clinical practice raises concerns regarding the acquisition of spectral references and the quality control and stability of antibody cocktails. Recent evidence suggests potential cocktail instability within a short period of only 24 h after preparation [33]. Therefore, it is essential to establish the quality of the antibody cocktail for clinical use, whether conventional or spectral flow cytometry is used.…”
Section: Discussionmentioning
confidence: 99%
“…panels to detect MRD in AML have recently produced a growing interest. For example, Soh et al proposed a 27-color panel to be run on a 5-laser spectral flow cytometer, and even Cytek Biosciences launched its first commercially available 20-color AML kit[33,34]. Our work shows important differences to these assays, as it exclusively features extensively validated antibody clones and focuses on most important LAIPs.…”
mentioning
confidence: 99%
“…The availability of new technologies such as CyTOF mass spectrometry and full-spectrum flow cytometry (FSFC) has demonstrated the capacity to utilize many markers (up to 27 colors) for AML MRD. 84 85 Additionally, by increasing the number of events from 1 million to 10 million, the sensitivity of MRD assay can easily be reached to as high as 2 × 10 −6 (0.0002%) MRD detection. 63 Thus, the recent availability of new flow cytometry technologies and newer dyes has improved the assay sensitivity and specificity for MRD assessment by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…A particularly useful study reported a 27-color single-tube assay using a 3-laser Cytek Aurora for detection of measurable residual disease in patients diagnosed with acute myeloid leukemia. 16 The lower limit of detection for identifying abnormal myeloblasts was 0.0013% in limiting dilution studies, indicating excellent sensitivity of spectral flow cytometers for detecting rare cell types. Importantly, this study also compared the 27-color panel against an 8-color multi-tube assay run a BD Canto II and found the two assays to be concordant in terms of cell type identification.…”
Section: Advantages Of Spectral Flow Cytometrymentioning
confidence: 91%
“…Given the recent deployment of spectral flow cytometry in clinical settings, there are limited use cases to draw upon. A particularly useful study reported a 27‐color single‐tube assay using a 3‐laser Cytek Aurora for detection of measurable residual disease in patients diagnosed with acute myeloid leukemia 16 . The lower limit of detection for identifying abnormal myeloblasts was 0.0013% in limiting dilution studies, indicating excellent sensitivity of spectral flow cytometers for detecting rare cell types.…”
Section: Clinical Applications Of Spectral Flow Cytometrymentioning
confidence: 99%